Obstacles Facing Arbitration in Jordanian Legislation: A Critical Analytical Study - Deab, Ghaith Yousef Najeeb (Journal of Economic, Administrative and Legal Sciences, 2022)
Arbitration is generally considered one of the preferred means for settling disputes between parties outside the framework of the judicial system, because of the latter’s negatives that would move away from it, and turn to a legal system that enjoys advantages and advantages that qualify it to play this role. This would limit its effectiveness and development, and Jordan is one of the countries that have made strides in the field of arbitration, as it dealt with the arbitration process through Arbitration Law No. 31 of (2001) and its amendments. However, the arbitration process may face some obstacles that reduce the advantages of this law And limit its effectiveness for some of the parties to the arbitral process, and accordingly, the arbitration process may face some obstacles at the international level and affect the credibility of the arbitration law, and it is possible that these obstacles face the arbitration parties during or after the arbitration process, and by extrapolating and analyzing some provisions of the arbitration law and the laws related to the arbitration process, We find that the Jordanian law did not address this legislative shortcoming, and through this research we will try to shed light on the shortcomings and then find some proposals and effective solutions to these obstacles. These obstacles include subjective and procedural obstacles, such as the absence of a specialized arbitration department in national courts and the lack of prompt consideration of these cases, and objective obstacles facing arbitration. This research was based on the critical analytical approach by examining the legal texts of the Jordanian Arbitration Law to highlight the obstacles facing Arbitration, and the research concluded with results, the most important of which is that no legislation mentioned the creation of a specialized department concerned with arbitration, in order to avoid procedural obstacles that would reduce the effectiveness of arbitration in light of the absence or weakness of the infrastructure of the judicial system in most countries, and no legislation referred to it. Provided that the action for nullity or any action related to arbitration shall be treated as one of the urgent cases. The researcher recommended the necessity of amending the legal texts so that the treatment of the problems that occur during the arbitral process in the first stage is assigned to the arbitral tribunal itself, at the very least. relating to the jurisdiction of the arbitral tribunal or not, and assigning it to the arbitral tribunal itself, at the very least.